Analisis Target Costing Dalam Upaya Pengurangan Biaya Produksi Beras Untuk Peningkatan Laba Perusahaan pada Penggilingan Padi Surya Agung - Saputra, Anggara; Febri Darmayanti, Elmira; Padwa Sari, Gustin (Universitas Muhammadiyah Metro, 2025)
Rice milling aims to produce rice, which is a daily necessity and is very important for the heterogeneous Indonesian society. The Central Bureau of Statistics reported that rice crop productivity in Indonesia increased to 52.56 ku/ha, placing Indonesia in third place globally after China and India. Surya Agung Rice Mill is a rice factory established in 2010 and located in Purwodadi Village. Rice classification according to SNI 6128:2015 consists of four categories, namely premium rice, medium 1, medium 2, and medium 3. Surya Agung Rice Mill produces rice in the premium, medium 1, and medium 2 categories. The results of the study indicate that the application of target costing can significantly increase net profit. Considering the problem of profit fluctuations at Surya Agung Rice Mill in recent months, as well as changes in raw material prices, high production costs, and slow operational processes, this study aims to update the GAP from previous studies.